Morpho-histological Study of the Digestive Tract and the Annex Glands of Chinchilla laniger - Călin Daniel Călămar; Silvia Pătruică; Gabi Dumitrescu; Marian Bura; Ioan Bănăţean Dunea; Marioara Nicula (Scientific Papers Animal Science and Biotechnologies, 2023)
No detailed histological study of the segments of the digestive tract and of the post-diaphragmatic annex glands of Chinchilla laniger is available in the literature, to our knowledge. The study presented draws attention to the morphological characteristics of the digestive tract and their involvement in the digestive process, with important implications for the composition of formula diets. Histological study of the digestive tract and annex glands (liver and pancreas) of Chinchilla laniger shows no major differences from other mammals. The walls of the oesophagus, stomach and intestine are composed of four layers: the mucosa, sub-mucosa, muscularis mucosa and serosa (the fourth layer of the oesophagus being called the adventitia). A noteworthy feature of the species is the generous development of the caecum in proportion to body size, a characteristic shared with other rodent species.